Essential Oil-Rich Chinese Formula Luofushan-Baicao Oil Inhibits the Infection of Influenza A Virus through the Regulation of NF-κB P65 and IRF3 Activation. (30th August 2021) - Mao, Xin; Gu, Shuyin; Sang, Huiting; Ye, Yilu; Li, Jingyan; Teng, Yunxia; Zhang, Feiyu; Ma, Qinhai; Jiang, Ping; Yang, Zifeng; Huang, Weizhong; Liu, Shuwen
Abstract : Background . Luofushan-Baicao Oil (LBO) is an essential oil-rich traditional Chinese medicine (TCM) formula that is commonly used to treat cold, cough, headache, sore throat, swelling, and pain. However, the anti-influenza activities of LBO and the underlying mechanism remain to be investigated. Methods . The in vitro anti-influenza activity of LBO was tested with methyl thiazolyl tetrazolium (MTT) and plaque assays. The effects of LBO on the expressions of viral nucleoprotein and cytokines were evaluated. In the polyinosinic-polycytidylic acid- (Poly I: C-) induced inflammation model, the influences of LBO on the expression of cytokines and the activation of NF- κ B P65 (P65) and interferon regulatory factor 3 (IRF3) were tested. After influenza A virus (IVA) infection, mice were administered with LBO for 5 days. The lung index, histopathologic change, the expression of viral protein, P65, and IRF3 in the lung tissue were measured. The levels of proinflammatory cytokines in serum were examined. Results . In vitro, LBO could significantly inhibit the infection of IVA, decrease the formation of plaques, and reduce the expression of viral nucleoprotein and cytokines. LBO could also effectively downregulate the expression of interleukin-1 β (IL-1 β ), interleukin-6 (IL-6), and interferon- β and the activation of P65 and IRF3 in Poly I:C-treated cells. In the IVA-infected mice model, inhalation of LBO with atomizer could decrease the lung index, alleviate the pathological injury in the lung tissue, and reduce the serum levels of IL-1 β and IL-6. LBO could significantly downregulate the expression of viral protein (nucleoprotein, PB2, and matrix 2 ion channel) and the phosphorylation of P65 and IRF3 in the lungs of mice. Conclusion . The therapeutic effects of LBO on treating influenza might result from the regulation of the immune response of IVA infection. LBO can be developed as an alternative therapeutic agent for influenza prevention.